Untangling time-averaging in shell middens: Defining temporal units using amino acid racemisation. (June 2016) - Koppel, Brent; Szabó, Katherine; Moore, Mark W.; Morwood, Michael J.
Abstract: Time-averaging is a process that affects almost every form of archaeological deposit. The conflation of two or more units from different time periods masks the true temporal span of units which is hidden by post-depositional processes. The implications of this are obvious as archaeological material found in close stratigraphic association may differ in age by hundreds or thousands of years. Some sites have a greater tendency towards the effects of time-averaging, with shell middens being one of the more susceptible. Conventional approaches to midden excavation or analysis, however, do little to tackle the issue of time-averaging. Using amino acid racemisation (AAR), an intensive relative dating programme was undertaken on shell midden excavated from a potentially time-averaged midden deposit. This approach revealed temporally distinct units that had been conflated into one deposit resulting in shell specimens temporally separated by up to 6000 years being found in close stratigraphic association. The application of AAR allowed us to define the temporal parameters of the various comingled deposits, and in doing so isolate temporal units which showed very different depositional patterns. These contrasting units imply different depositional behaviours and in turn changes in site use through time. This new application of AAR offers a way to approach shell midden archaeology to expose instances and repercussions of time-averaging that were previously hidden. Highlights: Amino acid racemisation isolates a time-averaged deposit in a shell midden. Stratigraphically associated material separated by over 5000 years in age This method presents a way to deal with the issue of time-averaged shell middens.